Designing an 'optimal' domestic retrofit programme. Issue 7 (3rd October 2018) - Gillich, Aaron; Sunikka-Blank, Minna; Ford, Andy
ABSTRACT: The US Better Buildings Neighborhood Program (BBNP) consisted of 41 different versions of thermal retrofit programmes with a common structure and objectives. This created a natural experiment in thermal retrofit programme design. This paper uses qualitative interviews with programme organizers measured against third-party programme performance data to create a model of 14 programme steps that were common to all BBNP grantees. This model uses the experiences of programme organizers to define best-practice principles associated with each programme step. Five themes emerge from the programme steps: (1) programme design: local market features and suitable programme structures; (2) marketing and outreach: the processes of creating awareness versus personal engagement – how community-based social marketing is a key strategy in driving demand; (3) workforce engagement: the skills gaps across the supply chain; (4) financial incentives: the merits of grants versus loans – how to use them in combination; and (5) data and evaluation: best-practice techniques for both programme evaluation and enabling iterative programme adjustments. These principles create a template for an 'optimal' programme model for retrofit programmes with stated objectives similar to the US BBNP. The potential and limitations in extrapolating this model to UK retrofit markets are considered.